2021
DOI: 10.1038/s41598-021-92601-5
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome anchoring in Senegalese sole (Solea senegalensis) reveals sex-associated markers and genome rearrangements in flatfish

Abstract: The integration of physical and high-density genetic maps is a very useful approach to achieve chromosome-level genome assemblies. Here, the genome of a male Senegalese sole (Solea senegalensis) was de novo assembled and the contigs were anchored to a high-quality genetic map for chromosome-level scaffolding. Hybrid assembled genome was 609.3 Mb long and contained 3403 contigs with a N50 of 513 kb. The linkage map was constructed using 16,287 informative SNPs derived from ddRAD sequencing in 327 sole individua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
35
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(45 citation statements)
references
References 68 publications
9
35
1
Order By: Relevance
“…Interestingly, non-synonymous variants were mostly concentrated at exon 14 and to an extent at exon 1, which are part of its intracellular and extracellular domains, respectively, related to signal transduction and hormone reception. Moreover, we could not detect evidence of a duplication of the fshr gene in the Senegalese sole male genome reported by Guerrero-Cozar et al (2021), and therefore, the fshry allele appears to be the key factor for the male fate of the undifferentiated primordium. A similar SD mechanism has been reported in gray mullet, where an fshry allele including only two non-synonymous variants was identified as responsible for the male fate of the undifferentiated primordium (Curzon et al, 2021).…”
Section: Discussioncontrasting
confidence: 63%
See 4 more Smart Citations
“…Interestingly, non-synonymous variants were mostly concentrated at exon 14 and to an extent at exon 1, which are part of its intracellular and extracellular domains, respectively, related to signal transduction and hormone reception. Moreover, we could not detect evidence of a duplication of the fshr gene in the Senegalese sole male genome reported by Guerrero-Cozar et al (2021), and therefore, the fshry allele appears to be the key factor for the male fate of the undifferentiated primordium. A similar SD mechanism has been reported in gray mullet, where an fshry allele including only two non-synonymous variants was identified as responsible for the male fate of the undifferentiated primordium (Curzon et al, 2021).…”
Section: Discussioncontrasting
confidence: 63%
“…Guerrero-Cozar et al (2021) reported a broad genomic region (1.4 Mb) associated with sex at SseLG18 of S. senegalensis (Sse C12 in our study) using five full-sib families, compatible with a nascent XX / XY system. They suggested a SD mechanism with incomplete penetrance influenced by environmental factors since sex association was incomplete, and proposed fshr as the most promising master SD gene considering its role in gonad development and previous data from other species (Curzon et al, 2021).…”
Section: Discussionmentioning
confidence: 53%
See 3 more Smart Citations